THE EFFECT OF STORAGE TIME ON ROOM TEMPERATURE ON THE ABILITY OF VILLAGE CHICKEN EGGS - I. B. M. S., Wiguna; Wirapartha, M.; Wijana, I W. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the effect of storage time at room temperature on the hatchability of free-range chicken eggs. The study used a completely randomized design (CRD) with 3 treatments and 6 replications. Each replication used 5 free-range chicken eggs so that 90 eggs were used. The treatments used in this study were: P0 = Free-range chicken eggs (control), P4 = Free-range chicken eggs stored at room temperature for 4 days and P8 = Free-range chicken eggs stored at room temperature for 8 days. The variables observed in the study were: initial egg weight (grams), egg fertility (%), egg shrinkage (%), egg mortality (%) and egg hatchability (%). The results showed that the effect of storage time for free-range chicken eggs in P0, P4 and P8 treatments was not significantly different (P>0.05) on egg fertility. In the treatment of P4 and P8 the shrinkage of eggs was higher by 40.28% and 90.12%, respectively than the P0 treatment, statistically, the results were significantly different (P<0.05). In the P0 and P4 treatment egg mortality was 60.6% and 67% lower than P8 treatment, statistically showing significantly different results (P<0.05). The hatchability of eggs in P8 treatment was 55.15% lower than P0 treatment, statistically, the results were significantly different (P<0.05). The conclusion obtained from this study is that the length of storage of free-range chicken eggs at room temperature from the control treatment or without being stored, stored for 4 days and stored for 8 days there was a decrease in egg weight. The hatchability of free-range chicken eggs from egg storage at room temperature for 4 days and without storage or control had lower mortality and higher hatchability than storage of free-range chicken eggs at room temperature for 8 days. Keywords: village chicken eggs, incubator, long storage time , hatchability